Routine blood report and common laboratory parameters in COVID-19: Experience from Bangladesh - Islam, Md Khairul; Hossain, Mohammad Murad; Sharif, Md Mohiuddin; Hasan, Pratyay; Molla, Md Maruf Ahmed; Amin, Md Robed (Journal of Medicine, 2021)
Background: The present study aimed to describe the association of hematological parameters and common clinico-epidemiological features wit hdisease severity among COVID-19 patients. Methods: This is a hospital based observational study done in Dhaka Medical College Hospital from 01 July 2020 to 15 September 2020. Findings from hematological tests along with patient clinic-pathological features were recorded from a total of 309 COVID-19 patients. All the data were analyzed by SPSS 23.0 software. Results: Among the studied hematological parameters hemoglobin percentage, total WBC count, lymphocyte percentage, platelet count, CRP, serum ferritin, d-dimer, and ESRwere significantly associated with disease severity (p<0.05). Association was found between disease severity and other biochemical markers, such as AST, ALT, LDH, and serum bilirubin. Conclusion: With limited resources these cheap, yet highly indicative biochemical markers could be used to assess, treat, and prognose COVID-19 patients in Bangladesh. J MEDICINE 2021; 22: 132-138